Curriculum Development for Aqidah Moral Subjects in Madrasas - Pawelay, Zulkifli T.; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh (Journal La Edusci, 2024)
The curriculum is a crucial element in enhancing the quality of education. The curriculum is a cohesive structure consisting of interconnected components that mutually reinforce one other. The curriculum comprises objectives, instructional materials, procedures, and evaluation. Within this system, the curriculum will progress towards an educational objective by collaborative efforts among all of its sub-systems. In the event that one of the curriculum variables malfunctions, the curriculum system will operate at a suboptimal level. Furthermore, the execution of the curriculum necessitated meticulous planning and organization of all its components. Curriculum development aligns the existing curriculum with desired educational objectives, drawing from external and internal influences, in order to provide students with the necessary skills and knowledge to thrive in the future. The purpose of this study is to explain the process of developing the curriculum for the Aqidah Akhlak subject, as outlined in the Minister of Religion's Decree (KMA) number 183. This decree pertains to the curriculum for Islamic religious education and Arabic, while KMA number 184 of 2019 provides guidelines for curriculum implementation in madrasas. The aim is to create an innovative curriculum that is legally supported and serves as a framework for development. The features of madrasas include the cultivation of character, the promotion of moral fortitude, the provision of anti-corruption instruction, and the fostering of religious moderation.